Access to HIV/AIDS or TB care among refugees in Kampala, Uganda: exploring the enablers and barriers during the COVID-19 pandemic - George Palattiyil; Peter Kisaakye; Hadijah Mwenyango; Simon Katongole; Francis Mulekya; Dina Sidhva; Harish Nair; Paul Bukuluki (Elsevier, 2022)
The rapid spread of COVID-19 has overwhelmed the existing health care systems, finding it challenging to provide essential health services besides the COVID-19 response interventions. Refugees are disproportionately affected by the COVID-19 pandemic because of the barriers they face to access health care. However, there is limited research that investigates how access to HIV/AIDS or TB care services by urban refugees is affected during pandemics such as the COVID-19. This study adopted a cross-sectional survey utilizing quantitative (N=229) and qualitative data (26 in-depth interviews and 8 key informant interviews) held among urban refugees living in Kampala, Uganda. Results revealed that more females (75%) than males (25%) were able to access TB or HIV/AIDS services during COVID-19 related lockdowns. A decrease in queues, delivery of drugs through Village Health Teams (VHTs), proximity to health facilities, supply of necessities like food and the reception at the health facilities facilitated access to TB or HIV/AIDS services. On the other hand, restrictions on public transport, high transport costs, unemployment and subsequent poverty were barriers to access to TB or HIV/AIDS services. Results offer major insights into the effect of COVID-19 control measures on disruption of access to services particularly in relation to being able to access service points. The findings suggest that recognizing structural barriers to uninterrupted or continued access to HIV/AIDS or TB services during pandemics such as COVID-19 can go a long way in helping stakeholders to design measures that make it possible for more urban refugees to access HIV/AIDS or TB services.